COAL CHARACTERISTICS OF SAROLANGUN - PAUH REGION: Implication for Coalbed Methane potential - Asep Kurnia Permana (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The world energy crisis has effected the Indonesian energy supply, inspite of  Indonesia is rich in another potential geo- resources, such as Coalbed Methane (CBM), which can be used for solving this crisis. The geology and coal characteristics of the Muaraenim Formation in Sarolangun - Pauh region, suggest that the Coalbed methane resource in this area is prospective. Detailed organic geochemical and petrographical study, using fresh surface and subcrop samples of coal was conducted. Petrographically, the coal mainly consists of vitrinite group, and is essentially composed telovitrinite, telocolinite, and detrovitrinite, with rare to sparse inertinite, and minor exinite and mineral matter. A geochemical result indicates the range of volatile matter content is from 13.39% to 33.50%, total sulphur from 0.11 to 2.38%, ash between0.68% and 52.4%, and moisture 18.01 up to 40.18% , with vitrinite reflectance values ranges from 0.35% to 0.47% . Furthermore the feature of micro-cleats or micro-cracks from SEM analysis are dominated by strike lines although some curved and sub-curved lines are also present. Open microcleats are predominant compared to close microcleats. Based on Barbara and Winter diagram, coalbed methane content derived from the Sarolangun- Pauh coal seam is expected to be low - moderate level, with methane content is present from 2.89 m3/t to 6.02 m3/t. SBC coalfield area shows that gas content is around 338.001, 354.6234 scf, Lubuk Napal is 743.232.370, 6576 scf, whilst the Sungai Dingin about 419.343,508.7245 scf. Keywords : coal characteristics,  Sarolangun-Pauh  Region, coalbed methane (CBM).